DEVELOPMENT OF VERTICAL-AXIS WIND TURBINE MODELS AS STRENGTHENING FOR SUSTAINABLE RENEWABLE ENERGY - Kenneth Sutjiawan; Tota Pirdo Kasih; Rudy Susanto; Noviando Yuliando; Evan Tanuwijaya (JURNAL EDUCATION AND DEVELOPMENT, 2024)
The use of electricity in the world continues to increase over time, the main source of producing electricity in the world is coal which is a basic material that takes a long time to form. Since 2021, British patrol has recorded that coal supplies in the world are available at 1,074,108 million tonnes. In Indonesia, coal still provides 60% of the country's electricity supply and the other 40% uses other energy such as water, steam, gas and other energy. New renewable energy development goals through the Sustainable Development Goals (SDG) in utilizing wind energy through vertical axis wind turbines. The research made three turbine models with different shapes, which then collected voltage data with an air compressor. The experimental results show that the average voltage generated by the two turbine models is 240 mV and 229 mV respectively. For the third model using two sampling methods obtained 353 mV and 292 mV. The use of vertical shaft wind turbines can be used in urban areas, especially in some tall buildings and parks. Research can still be developed by adding several other factors such as wind speed, turbine rotation speed and the aerodynamics of the turbine shape. and using a dc generator that requires a small torque so that it can increase the electric power produced. (KS)